2017
DOI: 10.1101/224360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin-release of the long ncRNA A-ROD is required for transcriptional activation of its target gene DKK1

Abstract: Long non-coding RNAs (ncRNAs) are involved in both positive and negative regulation of transcription. Long ncRNAs are often enriched in the nucleus and at chromatin but whether chromatin-release plays a functional role is unknown. Here, we used epigenetic marks, expression level and strength of chromatin interactions to group long ncRNAs and find that those engaged in strong chromatin interactions are less enriched at chromatin in MCF-7 cells, suggesting a functional involvement of chromatin-release of long nc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Regulated splicing can further assist in "releasing" the RNA from one compartment to another, allowing precise timing of its functional activity. For instance, a recent study has found that release from chromatin is essential for function of lncRNA A-ROD (Ntini et al 2018). For PCGs, regulated nuclear retention through regulation of splicing has been shown to orchestrate trans-lation and protein accumulation in several contexts (Ninomiya et al 2011;Mauger et al 2016;Naro et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regulated splicing can further assist in "releasing" the RNA from one compartment to another, allowing precise timing of its functional activity. For instance, a recent study has found that release from chromatin is essential for function of lncRNA A-ROD (Ntini et al 2018). For PCGs, regulated nuclear retention through regulation of splicing has been shown to orchestrate trans-lation and protein accumulation in several contexts (Ninomiya et al 2011;Mauger et al 2016;Naro et al 2017).…”
Section: Discussionmentioning
confidence: 99%